Optimizing Science Laboratory Management for Enhanced Student Learning Outcomes: Mengoptimalkan Manajemen Laboratorium Sains untuk Hasil Belajar Siswa - Efendi, Nur; Jayanti, Afifa Sofi Laras (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Laboratory management is vital for improving science education, yet many institutions struggle to optimize these resources. Specific Background: Effective management enhances student interest and practical skills in natural sciences, but inadequate management leads to underutilization of laboratory facilities, negatively impacting learning experiences. Knowledge Gap: While the importance of laboratory management is acknowledged, studies on specific practices and their effects on student engagement in natural science remain limited. Aims: This study explores management practices in a natural science laboratory and their implications for educational outcomes. Results: Findings reveal that planning, organization, implementation, supervision, and evaluation are poorly executed, resulting in incomplete documentation and minimal follow-up. Although practical activities spark student interest, systemic issues hinder their effectiveness. Novelty: The research provides new insights into the operational challenges of laboratory management in a specific educational context. Implications: Enhanced management strategies are necessary to improve resource allocation and laboratory utilization, fostering student engagement and skill development in natural sciences. Highlights : Critical Role: Effective laboratory management enhances student interest and practical skills in science education. Systemic Issues: Inadequate management practices lead to underutilization of laboratory resources, negatively impacting learning experiences. Need for Improvement: Enhanced strategies are essential for optimizing resource allocation and fostering student engagement in natural sciences. Keywords: laboratory management, science education, student engagement, practical skills, educational outcomes